The Impact of ICT on the Personal Self‑Development of Students - Turganbayeva, Botagul Altayevna; Moshkalov, Altynbek (Pedagogika, 2013)
The article focuses on the impact of information and communication technologies on the students’ self-development, analysis of the degree of the development, and attempts to identify controversy in the system of higher education today. The results of experiment are shown in the paper. Self-development, in our understanding, is a purposeful activity of the individual aimed at improving the quality of their skills and abilities, that is, self-improvement.